2007
DOI: 10.1093/jn/137.3.548
|View full text |Cite
|
Sign up to set email alerts
|

(n-3) PUFA Alter Raft Lipid Composition and Decrease Epidermal Growth Factor Receptor Levels in Lipid Rafts of Human Breast Cancer Cells1,2

Abstract: To determine the mechanism by which the (n-3) fatty acids (FA) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) decrease proliferation and induce apoptosis in MDA-MB-231 human breast cancer cells, we examined the effects of EPA and DHA on the lipid composition of lipid rafts as well as epidermal growth factor receptor (EGFR) raft localization and phosphorylation. (n-3) FA (a combination of EPA and DHA) inhibited (P < 0.05) the growth of MDA-MB-231 cells by 48-62% in the presence and absence, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
197
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 250 publications
(212 citation statements)
references
References 41 publications
12
197
0
2
Order By: Relevance
“…The focus of this article is on the CXCR4-CXCL12 axis. The similar structures and functions of the other chemokine receptors, coupled with the fact that other cell surface molecules such as endothelial growth factor receptor and interleukin-2 receptor are displaced by n-3 PUFA treatment (29,30), suggest that other surface molecules that support migration may be affected in the same manner. This would be particularly true for molecules that require the lipid raft domains for signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of this article is on the CXCR4-CXCL12 axis. The similar structures and functions of the other chemokine receptors, coupled with the fact that other cell surface molecules such as endothelial growth factor receptor and interleukin-2 receptor are displaced by n-3 PUFA treatment (29,30), suggest that other surface molecules that support migration may be affected in the same manner. This would be particularly true for molecules that require the lipid raft domains for signaling.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the urokinase-type plasminogen activator (uPA) and metalloproteinases (MMPs) are involved in extracellular matrix disorganization leading to the release of angiogenic factors such as Vegf or fgf, allowing the sprouting of new blood vessels and ultimately extra-and intravasation (13)(14)(15). Several studies have shown that lipid rafts in the plasma membrane can play an important role in cancer cells when n-3 Pufas were added, as it altered the cholesterol levels and consequently cell migration, invasion and angiogenesis (16,17). the DHa-induced decrease in breast cancer cell invasion may also be due to inhibition of voltage-gated na + channels (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of DHA or EPA into the cellular plasma membrane results in alterations of signaling patterns (Shaikh et al, 2004). The conformational changes induced in the plasma membrane also render certain surface receptors inaccessible to the ligand (Li et al, 2005;Schley et al, 2007). Additionally, DHA and EPA inhibit metastasis of MDA-MB-231 xenographs in mice to bone through targeting of CD44, the another prometastatic surface molecule (Mandal et al, 2010).…”
Section: Fish Oilmentioning
confidence: 99%